Contratto di rete e riposizionamento delle PMI: una lettura coordinata degli aspetti civilistici e fiscali - Arrigo, Tommaso; Tassani, Thomas (Piccola Impresa / Small Business, 2016)
This paper details the legal nature of the Contratto di rete (CR) introduced by the art. 3 comma 4-ter law 09/04/2009 n. 33 and is divided into two parts concerning civil and taxation profiles. The part of CR’s civil profile analyzes the main characteristics and how does it differentiates from the other legal tools of inter-firm relationships, with particular attention to his flexibility and limited responsibility of the common fund of the networks, also in regard of principle of the freedom of enterprise and Horizon2020 grant procedures. The taxation of CR demands to take separately into account the negotiating models by which it can be closed and such as to derive alternative taxation models. The first one, based on the taxable status of the network, is regulated by ordinary tax rules for "entities", both for direct and indirect taxation. The second one, based on the creation of a fund but without taxable status, has a typical tax system of the forms of asset segregation although there are many tax issues related to the network activity.